Gambaran skor pediatric early warning score (pews) Pada pola rujukan pasien anak Di instalasi gawat darurat - Payzar - Wahyudi; Ganis - Indriati; Bayhakky - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
An early warning score for children like PEWS (pediatric early warning score) has an ability to identify clinical deterioration of children and intervension can be taken before children condition become worst. The rapid response like increasing monitoring of children or transferring to intensive care unit. The aim of this research was to described PEWS of each transferring method for children in emergency department. This research used 85 respondents who admitted to the hospital in emergency department during 14 March – 14 June 2014. The respondents were taken by consecutive sampling method where children 0 – 18 years old evaluated by PEWS and then followed where the children being transferred based on doctor advice. After that the result presented by simple frequency distribution. The analysis found that children who adviced to went home have score ≤ 2, children who have score 3, 4, 5 transferred to inpatient ward and children who have score ≥ 6 transferred to NICU/PICU. This research recommended for nurses especially nurses at emergency department in a hospital to use PEWS to anticipate clinical deterioration of children in emergency department. Key words : clinical deterioration, PEWS, transferring method